Modeling and predictability of exchange rate changes by the extended relative Nelson-Siegel class of models - Hokuto Ishii (International Journal of Financial Studies, 2018)
This paper investigates the predictability of exchange rate changes by extracting the factors from the three-, four-, and five-factor model of the relative Nelson-Siegel class. Our empirical analysis shows that the relative spread factors are important for predicting future exchange rate changes, and our extended model improves the model fitting statistically. The regression model based on the three-factor relative Nelson-Siegel model is the superior model of the extended models for three-month-ahead out-of-sample predictions, and the prediction accuracy is statistically significant from the perspective of the Clark and West statistic. For 6- and 12-month-ahead predictions, although the five-factor model is superior to the other models, the prediction accuracy is not statistically significant.
Keywords: E47; F31; G17; 330; predictability; exchange rate; uncovered interest rate parity; yield curve model